The Integrative Framework between the Theory of Constraints and the Approach to the Cost of Activity (ABC) to Reduce Costs (An Applied Study) - Riyam Majid Khazaal (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The research mainly aims to achieve integration between the theory of constraints and the entrance to the cost of activity ABC to reduce unnecessary and unjustified costs in that complies, and this is done by deleting or canceling non-value-adding activities or merging them with other activities to help make the cost of products as low as possible and excellence over competitors. The research was applied in the Electronic Industries Company. Research reached a set of conclusions, the most important of which was that integration can be achieved between the theory of constraints and the entrance of ABC under the strategic approach to cost management, as both the theory of constraints and the entrance to costs based on activities represent alternative schemes for the model of building the productive structure of any institution. The ABC entrance It takes the information used in the theory of constraints and adds a monetary value to it and the causes of resource cost can be used to track the cost of resources on the activity that is a constraint and this cost can be divided by the causes of the cost of the activity.